Said Nursi's Thoughts and Its Contribution in Mainstreaming Moderation at Islamic Higher Education in Indonesia - Faiz, Muhammad (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2023)
This research focuses on the study of the spectrum of Said Nursi’s thought who became an important figure in the dynamics of Islam in Turkiye during the transitional period leading up to the collapse of the Ottoman Caliphate and the founding of the Republic of Turkiye. Said Nursi with the cultural movement "Risale-i Nur" prefers to inflame meaningful jihad as the path of his da'wah struggle rather than face to face confrontation against the newly established secular government of the Turkish republic structurally and radically. This paper will also focus on studying the current Risale-i Nur movement which began to be officially printed in Turkiye in the 1950s and then, 50 years later, around the 2000s, it has spread to hundreds of other countries, including Indonesia. The indications of this can be seen in the translation of the books "Risale-i Nur" into more than 150 world languages. The methodology used in this study is library research with literature sources related to Said Nursi's spectrum of thought and the Da'wah movement of the Risale-i Nur community as the main object of research. In addition, this research was also carried out through interviews with informants who were directly related to the research focus. In the Indonesian context, the Risale-i Nur movement can be studied through the center for the study of Nursi's thoughts which is under the auspices of the Nur Semesta Foundation and the publishing institution Risalah Nur Press. This study also explores reading corners and centers for the study of Said Nursi and his works in several Islamic colleges and universities, both private and public. This study concludes that Said Nursi Corner is a symbol of the moderate movement that contributes to developing knowledge, solidarity in social life and fraternal networks and as an inspiration for lecturers and students to explore the character of Said Nursi and his phenomenal work Risale-i Nur in mainstreaming moderation in Indonesia.